2014 residential wood combustion survey: Results overview and spatial allocation of emissions estimates. (1st February 2019) - Swab, Christopher; Allen, Philip; Armitage, Sarah; Biberic, Aida
Abstract: Through the use of monitoring, modeling, and emission inventories, the Oregon Department of Environmental Quality (DEQ) has identified residential wood combustion (RWC) as a significant source of air pollution in Oregon. Detailed emission inventories provide the best source of information to inform pollution reduction strategies. In order to refine and improve state and local RWC emission inventories, DEQ contracted with the Portland State University Survey Research Lab to perform a telephone survey on RWC in the Portland metro area. The goal of the project was to 1) quantify these emissions by type and location, and 2) to spatially allocate these emissions to US Census blocks in the study area and other parts of the state. Results, based on 1061 residences surveyed, showed that 4.3% of respondents burned wood for primary heating and 17.8% burned wood for secondary (backup heating or aesthetics) purposes. Primary burners burned four times more wood on average per device than secondary burners. As such, even though there were fewer primary burners they burned 51% of the total wood fuel combusted. The breakdown of estimated emissions of particulate matter 2.5 μm or less (PM2.5 ) from primary and secondary burners is nearly even, with 46.5% of emissions coming from primary burning and 53.5% of emissions coming from secondary burning. Uncertified woodstoves and inserts are the source of just over half (50.5%) the emissions in the Survey area, followed by emissions from certified woodstoves and inserts (26.3%), fireplaces (21.5%), pellet stoves (0.9%), and fire-log burning (0.8%). Survey results for burning activity and housing type showed good correlation, and were mapped to US Census housing data (units in structure) for block-groups. The Survey results also showed differences in burning behavior between urban/suburban and rural areas. This distinction coupled with housing types provided a method of spatial allocation for RWC activity and emissions that could be a useful tool for other states and regions. Highlights: Local survey links primary and secondary residential wood heating to housing type. US Census provides record of housing type information by block group. Block groups classified as urban/suburban or rural based on block group size. Wood heating emissions by housing allocated to urban/suburban or rural block groups.